Glimpses of indian economic policy - Patel, I. G. (New Delhi, 2006)
This is a biographical account of I.G. Patel's views on the evolution of Indian economic policy over the past five decades. His discussion of events in modern India's economic history are highly relevant for understanding contemporary policy issues that are often hotly debated.
Keywords: Economic policy-India